Autochthonous North American Leprosy: A Second Case in Canada - Prenilla Naidu; Rahul Sharma; Jamil N. Kanji; Vilma Marks; Arienne King (MDPI AG, 2021)
Autochthonous leprosy was reported in the Southern USA in 2011 and has comprised an average of 34% of new cases from 2015 to 2020 in that country. We report a similar case in a patient from Western Canada. A 50-year old male patient presented with a four-year history of a chronic rash. Pathology stains revealed acid-fast bacilli prompting specialist referral. Examination was suspicious for leprosy, which was confirmed on slit skin smears and molecular testing. The patient responded well to treatment. Genotypic testing mapped the organism to the 3I-2 SNP type, which is of European origin and is the type found in implicated armadillo species in North America.